2015
DOI: 10.1631/jzus.a1400105
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of piston-pin lubrication considering the effects of structure deformation and cavitation

Abstract: Abstract:Running conditions for piston pin boss bearing have become very severe due to the high combustion pressure and piston temperature increase over the past ten years. The aim of this paper was to analyze the friction and lubrication characteristic of piston pin boss bearings and a connecting rod small end bearing. This paper provided a comprehensive analysis of piston pin based on a multi-body dynamic model which considers the oil film cavitation and structure deformation. Effects of different lubricatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 20 publications
(22 reference statements)
1
4
0
Order By: Relevance
“…10b, for the piston with pin hole radius enlarging rate b = 1,6410 -4 , the wear marks on area B of the top surface of the pin hole were significantly mitigated, with no lubricant deposits left on the surface. These above results are consistent with Baꞌs research [11] by using multi-body dynamics model and piston pin hole lubrication model, in which it is concluded that rough contact pressure of parabola contour is smaller than that of square contour, and the wear of parabola contour is smaller. The increasing of the pin hole radius enlarging rate, the enlarging of the piston pin hole conforms to the deformation of piston pin, the contact pressure is reduced, and the wear is reduced.…”
Section: Hydraulic Pulsating Fatigue Tests Of Piston Pin Holessupporting
confidence: 91%
See 1 more Smart Citation
“…10b, for the piston with pin hole radius enlarging rate b = 1,6410 -4 , the wear marks on area B of the top surface of the pin hole were significantly mitigated, with no lubricant deposits left on the surface. These above results are consistent with Baꞌs research [11] by using multi-body dynamics model and piston pin hole lubrication model, in which it is concluded that rough contact pressure of parabola contour is smaller than that of square contour, and the wear of parabola contour is smaller. The increasing of the pin hole radius enlarging rate, the enlarging of the piston pin hole conforms to the deformation of piston pin, the contact pressure is reduced, and the wear is reduced.…”
Section: Hydraulic Pulsating Fatigue Tests Of Piston Pin Holessupporting
confidence: 91%
“…Zhang et al [10] mentioned that the special-shaped pin hole profile could improve the stress distribution on the piston pin hole surface, preventing the stress concentration, and reducing the risk of fatigue cracking in the piston pin hole. Ba et al [11] conducted comparative study of the curved profile of the piston pin hole with the conical profile structure, and the results indicated that the curved profile structure led to a larger contact area between the piston pin hole and the pin, thus lowering contact friction and the resultant friction power consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in order to prevent local partial contact due to deformation of pin bosses and piston pins, tapered pin bosses have been used for ensuring clearance at their inner end surface. These parts are designed on the basis of theoretical calculations such as those obtained by CAE tools [1][2][3][4][5][6]. More accurate experimental data are needed to further improve CAE techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The interference fit joints consists of shaft that is larger than a tube when inserted into the joint. The press-fit parts requires interference by the tube expansion radially and reduction of the diameter of the shaft of the joint [4]. This process is to use to ensure that stresses are uniformly distributed in the tube by the insertion of the pin into the joint.…”
Section: Introductionmentioning
confidence: 99%
“…Piston pin used for joining the piston and cylinder liner of different inner diameters for varying joint strengths[4].…”
mentioning
confidence: 99%